Implementasi Peraturan Menteri Perhubungan Republik Indonesia Nomor PM 75 Tahun 2015 Tentang Penyelenggaraan Analisis Dampak Lalu Lintas (Studi Kasus Program Area Traffic Control System) di Kota Denpasar - Paramitha, Ida Ayu Pradnya; Wismayanti, Kadek Wiwin Dwi; Winaya, I Ketut (CITIZEN CHARTER, 2020)
ABSTRACT Regulation of Transportation Minister Republic Number PM 75 years 2015 concern about Implementation of Traffic Impact Analysis are explains required installation of infrastructure at each intersection in order to carry out traffic management with technology and coordinated. However, there are still problems faces during implementation such as the growth rate of motor vehicles along with the higher traffic congestion, high accident rates, and the lack of public knowledge.ThisEtypeEof research used isEdescriptiveEqualitative,dataIcollection techniquesiused areIobservation,iinterview, documentation, and teqniquesuofutriangulasi. The result analyzed with 3 aspects are have notibeen runningooptimally,obecause thereoareestill problems such as not having a clearer task for every operator’s tasks, principle, and functions, lack of experts with technological education background, often occurring server disruption to live streaming features, lack of socialization about the program and constrained by budgeting in the maintenance of the tools. Keywords : Area Traffic Control System Program’s. Denpasar City, Implementation of Policy